Acardia: Epidemiologic findings and literature review from the International Clearinghouse for Birth Defects Surveillance and Research - Botto, Lorenzo (2011)
Acardia is a severe, complex malformation of monozygotic twinning, but beyond clinical case series, very few epidemiologic data are available. The goals of this study were to assess the epidemiologic characteristics of acardia from birth defect registries in the International Clearinghouse for Birth Defects Surveillance and Research (Clearinghouse), and compare these findings to current literature. The study included 17 surveillance programs of the Clearinghouse representing 23 countries from North and South America, Europe, China, and Australia. Anonymized individual records with clinical and demographic data were reviewed centrally by clinical geneticists. A literature search was performed. A total of 164 cases of acardia were reported from an underlying cohort of 21.2 million births. Of these, 23% were elective pregnancy terminations. Rates did not vary significantly by maternal age. For many cases, information on pregnancy exposures and genetic testing was missing. However, these limited data did not suggest high rates of chronic illnesses (diabetes, seizure disorders) or lifestyle factors such as smoking. One case had trisomy 13. Major malformations were reported in 2.4% of co-twins. With some basic assumptions, the total prevalence of acardia was estimated at 1 in 50,000-70,000 births, and 1 in 200-280 monozygotic twins. In summary, acardia is a dramatic, probably underreported, and incompletely understood malformation. Studies on its epidemiology and etiology are challenging and still rare. An international collaboration of epidemiologists, clinicians, and geneticists is necessary to understand the etiology, pathogenesis, and occurrence of this severe malformation complex.